2018
DOI: 10.1002/nur.21868
|View full text |Cite
|
Sign up to set email alerts
|

Trends in bullying victimization by gender among U.S. high school students

Abstract: This research used four consecutive waves of data from the National Youth Risk Behavior Survey (YRBS) conducted by the Centers for Disease Control (CDC), to estimate linear time trends by gender in the prevalence of school and electronic bullying victimization among U.S. high school students (N = 61,042). Dependent variables were student self-reported school bullying victimization and electronic bullying victimization during the previous 12 months. Independent variables used to estimate multiple logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
53
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 39 publications
9
53
1
Order By: Relevance
“…The main findings of this study are we did not observe a downward trend in both forms of bullying victimization, and more female students reported being bullied compared with male students, both traditionally and electronically. These findings echoed the previous findings [8,9], and highlighted the gap between reality and the Healthy People 2020 goal on reducing bullying and identify female students as the priority group.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The main findings of this study are we did not observe a downward trend in both forms of bullying victimization, and more female students reported being bullied compared with male students, both traditionally and electronically. These findings echoed the previous findings [8,9], and highlighted the gap between reality and the Healthy People 2020 goal on reducing bullying and identify female students as the priority group.…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with the results from previous studies in U.S. high school students [6,8,16,17], in our study, the self-reported prevalences of being cyberbullied and traditionally bullied among female students are both higher than male peers across the survey cycles, indicating that there are sex disparities in traditional and cyberbullying. The underlying cause for the unchanged trends for both female and male students may be that existing anti-bullying initiatives could reduce verbal and physical bullying effectively, but not relational bullying [9]. Relational bullying victimization ranked as the top bullying form among U.S. adolescents, and females were more likely to be involved in relational bullying according to Health Behavior in School-Aged Children study [18].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the included articles (20 out of 23; 87.0%) examined the prevalence of bullying victimization among Asian-American youth. The rates of being bullied among this population range from 5 to 50% ( 1% of Asian-American high school students were victims of bullying at school in the past year, which was statistically lower than the percentage of white students (22.4%); 13.8% of Asian-American students report being electronically bullied in the past year, which was also lower than the percentage of white students (18.0%) (Pontes et al 2018). Meanwhile, according to the same study, Asian-American female students report being less likely than white female students to be bullied at school or electronically bullied, whereas there was no difference between Asian-American males and white males (Pontes et al 2018).…”
Section: Prevalence Of Bullying Victimizationmentioning
confidence: 78%
“…Nonetheless, results from three other studies do not fully echo with the findings (Mouttapa et al 2004;Pontes et al 2018;Wang et al 2016). The prevalence of school bullying victimization in the last year among Asian-American high school students (17.1%) was slightly lower than that in Hispanic students (17.5%) but higher than that in African-American students (12.8%) (Pontes et al 2018). Fourth-and 5th-grade Asian-American students in Southern California did not significantly differ from their non-Asian counterparts on experiencing bullying victimization (Wang et al 2016).…”
Section: Impacts Risk Factorsmentioning
confidence: 86%
See 1 more Smart Citation